A Clathrin-Related Protein, SCD2/RRP1, Participates in Abscisic Acid Signaling in Arabidopsis - Hou, Bingzhu; Shen, Yuanyue (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) plays important roles in many aspects of plant growth and development, as well as various stress adaptation. Although much progress has been made toward understanding the molecular mechanisms for ABA homoeostasis and signaling, how plant cells integrate ABA trafficking and signaling to regulate plant developmental processes is poorly understood. Manipulation of AtSCD2/RRP1 expression affects ABA sensitivity in seed germination and seedling growth, as well as several ABA transporter gene transcripts and ABA contents. RNA-seq analysis of the Arabidopsis transgenic mutants suggests a link of SCD2/ RRP1 protein to ABA signaling via PP2C protein. AtSCD2/RRP1 recruits its N- and C- terminals to separately interact with both AtPYR1 and AtPP2C1 on the plasma-membrane, and AtSCD2/RRP1 is genetically upstream of AtABI1. Interestingly, ABA may inhibit the interaction of AtSCD2/RRP1 with AtABI1, while ABA cannot affect the interaction of AtSCD2/RRP1 with AtPYR1. Manipulation of Arabidopsis RRP1 expression affects a set of ABA transporter gene expression and ABA contents. These results suggest that AtSCD2/RRP1 takes part in Arabidopsis seed early development and growth potentially through CME (clathrin-mediated endocytosis)- and CCV (clathrin-coated vesicle)-mediated ABA trafficking and ABA signaling. These new findings uncover a deep mechanism by which cells regulate plant developmental processes through ABA.